Prevalence and Determinants of Drugs Abuse Among Youth in Hyderabad, Sindh, Pakistan - Taniya Ahmed; Rashid Wassan; Dr. Naveed Ali Qadri; Shayan Ahmed (Journal of Management Practices, Humanities and Social Sciences, 2022)
The current qualitative research focuses on substance abuse and addiction among young people as a primary area of investigation. This study aimed to shed light on the substance that young people in Hyderabad, Sindh, take the most frequently and the most critical factors contributing to drug addiction. The research was carried out by proceeding to a mental hospital drug rehabilitation ward in Hyderabad, Sindh, and conducting face-to-face interviews with a total of 36 participants, ranging in age from 16 to 22, including both males and females. The participants were selected using a technique known as purposeful sampling. The study's findings indicated that alcohol, heroin, and ice drugs are the three substances used by young people with the most significant prevalence. In addition, researchers found that intra-personal factors, such as problems with mental health and entertainment, and extra-personal factors, such as peer pressure and the influence of the neighborhood, as well as the impact of the media, are the primary contributors to substance abuse among young people. According to the findings of the study, one preventative measure that may be taken to lower rates of drug addiction among young people is for parents, schools, governments, and other social groups to work together to educate young people about the negative consequences of drug consumption.